A103 META-ANALYSIS: NEOPLASIA OF THE POUCH IN PATIENTS WITH ULCERATIVE COLITIS POST ILEAL POUCH-ANAL ANASTOMOSIS. (21st February 2022) - Alazemi, K; Hussain, M; Hudson, D; Khanna, R
Abstract: Background: Ileal anal pouch anastomosis (IPAA) is often used for patients with severe ulcerative colitis that is refractory to medical treatment or for patients with neoplasia/dysplasia to maintain intestinal continuity. Patients with ulcerative colitis have an increased risk of developing dysplasia or colorectal cancer compared to the general population, however the need for pouch surveillance is debated. A meta-analysis was performed to identify the risk and prevalence of pouch related malignancy in patient with ulcerative colitis following IPAA. Aims: Our aim is to assess of the rate of dysplasia and malignancy post IPAA in patients with ulcerative colitis and also assess what the factors associated with developing malignancy post IPAA Methods: A search of Embase and Ovid MEDLINE was conducted to identify studies from 2014 to June 2021 that reported the incidence of dysplasia or malignancy following IPAA in patients with ulcerative colitis. Abstracts and conferences were not included in the search. The studies were assessed for relevance and data were extracted independently by two reviewers. Results: This analysis included 11, 268 patients with variable follow-up. The evidence was graded as low-certainty due to significant heterogeneity and low-quality studies. The pooled prevalence of carcinoma or dysplasia (low or high grade) in pouch or the rectal cuff was 0.4% [95% CI 0.2- 0.7]. However, in patients with prior colectomy for colorectal cancer the odds ratio was 32.20 [95% CI 15.58 - 66.53] for pouch malignancy. Significant heterogeneity and variability of the pooled studies was identified (I2 = 77.5%). Conclusions: Although the rate of dysplasia or malignancy was 0.4% for all IPAA, the odds ratio for these outcomes in patients with IPAA for prior malignancy was 32.20 [95% CI 15.58 - 66.53]. Further studies are required to validate these findings. Funding Agencies: None